On-Chip Electrochemical Analysis Combined with Liquid-Phase Electron Microscopy of Zinc Deposition/Dissolution. Issue 11 (26th November 2021) - Sasaki, Yuki; Yoshida, Kaname; Kuwabara, Akihide; Ikuhara, Yuichi
Abstract : Dendrite growth of Zn on the anode of Zn-based rechargeable batteries can cause short-circuiting. To avoid the formation of dendrites, the Zn deposition/dissolution behaviors and their dependence on the electrochemical conditions should be clarified. In this study, in situ transmission electron microscopy (TEM) observations using an electrochemical chip (e-chip) were conducted to visualize the initial stage of the electrodeposition of Zn on an anode. The electrochemical data corresponding to the in situ TEM observations were precisely and extensively analyzed. The combined optimized use of a potentiostat and transmission electron microscope enabled electrochemical electrodes to be isolated completely from the potential of the TEM column. This environment stabilized the electrodeposition process during the in situ TEM observations. Under constant-current mode, the electric potential was varied, resulting in the deposition of various amounts of Zn onto the Pt working electrode. Controlling the surface materials of the electrodes and the electrochemical conditions was important for in situ TEM observations of electrochemical reactions.